The impact of legislative regulation on animal epidemic prevention and control input: evidence from 13 main provinces of pig production in China - Liu, Wei; Tao, Jianping (Frontiers in Veterinary Science, 2025)
IntroductionThe issue of animal epidemic prevention and control has gained significant attention. Regulating and incentivizing farmers' animal epidemic prevention behaviors is vital for safeguarding national biosecurity. Previous studies have focused on the importance of animal disease prevention and control legislation but not examined the incentive of animal epidemic prevention behavior from the perspective of legislation. This study investigates the relationship between legislative regulation and farmers' animal epidemic prevention input, generating critical evidence for refining China's animal epidemic control framework and advancing the high-quality development of animal husbandry.MethodsUsing balanced panel data from 13 main pig-breeding provinces in China from 2006 to 2022, this study employs the Feasible Generalized Least Squares (FGLS) method to: (1) evaluate the impact of legislative regulation on pig farmers' animal epidemic prevention and control input; (2) investigate the changes in epidemic prevention and control input of pig farmers of different scales and the differences in the effects of laws and regulations of different legal hierarchies, and (3) examine the impact of law enforcement practices on the effect of textual legislation.ResultsLegislative regulation significantly increases animal epidemic prevention and control input, with the strongest effect on medium-scale farmers and no effect on large-scale farmers. The input-enhancing effect varies across laws and regulations of different legal hierarchies, with descending order: local administrative rules, central-level administrative regulations and divisional regulations, and local regulations. Heterogeneity analysis indicates that this input-enhancing effect of legislative regulation is only pronounced in regions with higher law enforcement on animal epidemic prevention and control.DiscussionThis study can also provide important inspiration for other developing countries. Governments should intensify legal literacy initiatives, enhance farmers' regulatory awareness, implement regionally differentiated prevention measures, strengthen adaptive enforcement capacities, and ultimately realizing synergistic welfare gains across economic, biosecurity, and animal wellbeing domains.